The Economics of Tobacco Taxation and Employment in Indonesia : Policy Note - World Bank Group (World Bank, Washington, DC, 2017)
This report is part of the Indonesia Tobacco Employment Studies implemented by the World Bank and the American Cancer Society. The findings from this report complement the findings from three closely-related reports focusing on specific segments of tobacco sector employment in Indonesia: tobacco farmers, kretek workers or “hand-rollers,” and tobacco manufacturing more broadly.